Seeding a Sustainable Future: How Youth and Women Quality Centers are Transforming Uganda’s Seed Landscape - Bomuhangi, Allan; Yila, Jummai O.; Nchanji, Eileen; Puskur, Ranjitha (International Rice Research Institute, 2024)
Ensuring equitable access to quality seeds of climate-resilient, high-yielding crop varieties is critical to enhancing agricultural productivity, contributing to food security, and improving the livelihoods of smallholder farmers. However, entrenched barriers such as limited mobility and lack of access to information and resources due to pervasive social norms have long hindered the widespread adoption of these varieties, particularly among marginalized groups like women. Work Package 6 of the CGIAR Seed Equal Initiative is pioneering a social behavior and communication change (SBCC) strategy in Butaleja district, Eastern Uganda, to influence farmers’ attitudes and practices towards using quality seeds. The strategy was co-created in a stakeholder workshop with private and public sector partners, including farmers, seed producers, market actors, agricultural service providers, and district government officials. This strategy was informed by the situation analysis comprising a review of secondary data and primary baseline data.